How can customers cope with cognitive demands of professional services? The role of employee coping support - Janina Garbas; Marah Blaurock; Marion Büttgen; Zelal Ates (Psychology & Marketing, 2023)
Even though researchers are increasingly acknowledging the dark side of customer participation (i.e., behavioral customer engagement), particularly in professional services with high cognitive demands that cause customer participation stress (i.e., negative psychological state resulting from the customer's overextension by required customer participation efforts), insights on how firms can effectively mitigate customer participation stress remains limited. Building on transactional stress theory, we investigate whether customers can effectively cope with the expected cognitive demands of professional services. Moreover, by introducing an adapted coping construct (i.e., coping support), we examine whether employees can provide coping support to help decrease customer participation stress. The findings of a time-lagged field study with customers of a large German bank (N0.167em=0.167em117) suggest that customer coping before the encounter cannot mitigate the effect of anticipated cognitive demands on customer participation stress. Instead, the results of both the field study and a follow-up experimental study (N0.167em=0.167em218) show that a certain set of employee coping support during service encounters is crucial. While focusing on action coping support is not ideal in situations with high cognitive demands, firms should advise their professional service employees to offer emotional coping support to attenuate the unfavorable effect of cognitive demands on customer participation stress.
Keywords: 650; cognitive demands; coping; customer engagement; customer participation stress; frontline employees; professional services; transactional stress theory